Aplicación de la señalética para fortalecer la seguridad industrial en el taller de Mecánica Industrial de la Unidad Educativa Tomás Oleas del Cantón Colta en el periodo académico 2017-2018 - Cartagena Yumbillo, Kleber Geovanny (2018)
The progress of nations has developed since the industrial revolution, which generated an impact on the creation of factories, the same thing happened with the world wars, which caused many deaths due to the deployment in the creation of war weapons. Reason for which labor accidents increased strongly within the factories and this is how industrial safety appears in the labor field with the purpose of reducing work accidents. Companies invest large amounts of money in staff training, to ensure the welfare of their employees. The present investigation analyzes this important aspect and it is included in the educational area because resources are used within the professional practice using laboratories and industrial workshops. The Tomás Oleas Educational Unit of the Colta Canton, forms technical baccalaureates that use laboratories daily and seeks to generate a safe environment. A diagnosis of the current situation was planned and executed, determining the requirement for Industrial Safety signage. For its implementation, signs were used in the following aspects: Obligation, Prevention, Prohibition and Evacuation; complying with established standards and technical specifications. With this investigation information of the current state of the workshop was collected, in addition, it was made directly where the facts occur, that is to say in the aforementioned institution, in conclusion the signage and industrial safety were implemented properly. Workshop personnel are recommended to keep the aforementioned indications, observe and comply with the rules established to safeguard their integrity.